Developmental Research: An Android-Based Arabic Language Learning Application as a Means to Improve Middle School Students' Learning Outcomes - Yusra Al amin; Zughrofiyatun Najah (WISE Pendidikan Indonesia, 2023)
This study aims to develop and evaluate an Android-based interactive learning application for Arabic language instruction for eighth-grade students. The objectives are: (1) to design an engaging Android-based learning tool for Arabic; (2) to assess the feasibility of the tool; (3) to examine the tool’s effectiveness in enhancing the learning process; and (4) to determine the impact on student learning outcomes before and after using the application. Employing a Research and Development (R&D) methodology, the ADDIE model was used for product development. The research results indicate that the developed application is accessible across all Android versions and has been validated by subject matter and media experts, achieving scores of 89.2% and 86.5%, respectively, confirming its high feasibility for classroom use. Effectiveness testing revealed moderate effectiveness, with small-scale and large-scale trials achieving effectiveness rates of 61.82% and 69.16%, respectively. Additionally, a paired T-test analysis showed a significant improvement in students' learning outcomes, with pre-test and post-test scores differing significantly (t = 21.03845 > tcritical = 1.699, p < 0.05). The results support the conclusion that the Android-based interactive media significantly improves Arabic language learning outcomes among eighth-grade students.